A comparative study and stiffness analysis of angular contact ball bearings under different preload mechanisms. (September 2017) - Zhang, Jinhua; Fang, Bin; Zhu, Yongsheng; Hong, Jun
Highlights: A comparison model for bearing under different preload mechanisms is built. The differences of two different preload mechanisms are discussed. The influences of inner ring interference, speed and load on stiffness are discussed. The model provides a theoretical foundation for the bearing-rotor system. Abstract: The dynamic performance of angular contact ball bearings is greatly affected by preload force and preload mechanisms. In the present research, a comparison model is built to analyze the stiffness of angular contact ball bearings under different preload mechanisms. In the first part, the elastic deformation of inner ring of bearing produced by assembling stress and centrifugal stress is calculated. Then the differences of two different types of preload on the action mechanism of bearings are discussed. Based on these, a comparative model of ball bearing and stiffness with respect to different preload mechanisms is proposed. Finally, the influences of the inner ring interference value, rotating speed and radial load on the bearing characteristics and stiffness are discussed in detail. The results show that under fix-positon preload, the bearing have a better stability of stiffness, and the inner ring interference value and rotating speed also have a significant influence on the bearing dynamic properties and stiffness. In addition, the proposed model is validated by comparing the results obtained by the proposed method with those from the other literatures and experiments.